The Causal Model between Academic Self-Efficacy and Academic Resilience on the Professional Identity of Student Teachers - Siriluk, Wipawee (SOCIAL SCIENCES RESEARCH AND ACADEMIC JOURNAL, 2025)
This objectives of this research were to: 1) examine the levels of academic self-efficacy, academic resilience, and professional identity among student teachers, and 2) analyze the causal model between academic self-efficacy and academic resilience on the professional identity of student teachers. This study employed a survey research methodology. Data were collected from 211 third-year student teachers from universities across Thailand and obtained through multi-stage random sampling. The data collection instrument was a questionnaire for students, consisting of an academic self-efficacy scale, an academic resilience scale, and a professional identity scale. The data were analyzed using descriptive statistics and structural equation models. The findings revealed that 1) the pre-service teachers demonstrated high levels in overall three characteristics: academic self-efficacy, academic resilience, and professional identity, and 2) the causal relationship model between academic self-efficacy, academic resilience, and professional identity showed good fit with the empirical data (χ2 (43, N = 211) = 58.46, p = .06, χ2/df = 1.36, CFI = .99, TLI = .98, RMSEA = .04, SRMR = .04). Academic self-efficacy had a direct effect on academic resilience but no direct effect on professional identity, while academic resilience had a direct effect on professional identity. Furthermore, academic self-efficacy had an indirect effect on professional identity through academic resilience.